On the Robustness of Idiosyncratic Volatility Effect - Barinov, Alexander (Management Science, 2025)
The idiosyncratic volatility (IVol) effect is robust to restricting the sample to New York Stock Exchange (NYSE) firms (once the proper listing indicator is used) and to excluding from the sample small, illiquid, and low-price stocks. The idiosyncratic volatility effect is also unlikely to stem from the short-run reversal, as the IVol effect stays significant for about six months and seems stronger for high turnover firms, which do not exhibit short-term reversal. The IVol effect also does not seem to weaken postpublication. This paper was accepted by Lukas Schmid, finance. Supplemental Material: The online appendix and data files are available at https://doi.org/10.1287/mnsc.2022.04140 .